Bioaccumulation Factor of Selected Heavy Metals in Zea mays - Aladesanmi, Omolara Titilayo (J Health Pollut, 2019)
BACKGROUND. Health risks arising from heavy metal pollution have attracted global attention. As a result, many studies on the accumulation of heavy metals in soil-plant systems have performed human health risk assessments. OBJECTIVES. We aimed to examine the ability of Zea mays (maize) to accumulate heavy metals and assess the bioaccumulation factor (BAF) by collecting, collating, and analyzing data on heavy metal concentrations in Zea mays. METHODS. This study reviewed the accumulation of five selected heavy metals, cadmium (Cd), chromium (Cr), lead (Pb), copper (Cu), and zinc (Zn) in soil and the corresponding BAF of Zea mays grown on those soils using a systematic search of peer-reviewed scientific journals. A total of 27 research works were reviewed after screening 52 articles for subject matter relevancy, including dumpsites, industrially polluted soils, inorganically fertilized soils, mining sites, smelting sites, municipal wastewater irrigated soils, and a battery waste dumpsite. RESULTS. Among the reviewed sites, concentrations of Cd and Cr were highest at a tin mining site, where prolonged mining, mineral processing and other production activities contributed heavy metal pollution in the soil. The soil at a battery waste dumpsite exhibited the highest Pb concentration, while the soil at a Zn smelting site presented the highest concentration of Zn. The highest soil Cu concentration was found in an area where sewage irrigation had been carried out over a long period. The BAF of the five heavy metals in Zea mays increased with the metal concentrations in the soil. The BAF of Cd, Cr, Pb, Cu, and Zn in Zea mays from the study areas fall within the ranges of 0–0.95, 0–1.89, 0–1.20, 0.011–0.99, and 0.03–0.99, respectively. Cadmium and Zn had the highest bioconcentration factors values in maize plants, likely due to their higher mobility rate compared to the other heavy metals. CONCLUSIONS. The study concluded that Zea mays is capable of accumulating high amounts of heavy metals, although accumulation of these heavy metals is influenced by multiple factors including soil texture, cation exchange capacity, root exudation and especially soil pH and chemical forms of the heavy metals. Zea mays should not be planted on metal-contaminated soils because of its potential to act as a hyperaccumulator. COMPETING INTERESTS. The authors declare no competing financial interests.